AIR MANCUR KERAMIK ( PRODUK INOVATIF TERINSPIRASI BENTUK JAMUR TIRAM ) - Prima Yustana (Institut Seni Indonesia Surakarta, 2020)
This research is aimed to a project of art as a means of developing the ideas that emerged from the oyster mushroom plant forms found in nature and cultivated. The author is very interested in the oyster mushroom because of the umbrella shape so that there appears in the artist mind an idea to visualize the form into another form that can have aesthetic elements and serves as a means maker cool atmosphere with the rush of water falling through the cracks form of oyster mushroom highly artistic in appearance. The process of making is by using the method of exploration, the process of creation, or formation, water pump engine assembly, analysis and presentation of the work. The data is obtained by looking at the existing references either from the literature or retrieve data directly on the object of research in the field. Documentation is done by using a photo camera or scanner tools such reproduction. The artwork is oriented to innovation of existing products in the market with fresh and new ideas from nature into a work that has a function as an ornamentalKeywords: fountain, oyster mushroom, ceramic.